Micro-structure and self-lubricant properties of powder mixed electrical discharge metal matrix composite coating. (August 2022) - Arun, Ilangovan; Yuvaraj, C; Sivakumar, A; Thamizhmanii, S
In present exploration, Electric Discharge Alloying/Coating (EDA/C) is made over duplex stainless steel as alloying elements of nickel, graphite, copper (electrode) and pyrolysis carbon from oil together with substrate material results in metal matrix composite coating. Coating possess average hardness value of 1018 HV 0.5 four times higher and lowered specific wear rate of 1.18 × 10 −5 mm 3 /N m with an improved average friction coefficient of 0.3 through Pin on Disc (POD) wear tester. Metallurgical properties of the coating are analysed through surface topography by 3D optical profilometer, coating microstructure over and across with elemental distribution are identified by electron microscope (SEM) attached with Energy-Dispersive X-Ray Spectroscopy (EDS). Phase transform from δ and γ of cementite with meta stable iron carbide appeared as austenitic structure are identified through Electron Probe Micro Analyser (EPMA) and by X-ray diffraction. This meta stable carbides together with alloying elements provides improved tensile and bonding strength at room temperature were else copper controls further phase transformation. Copper shows stick slip at lower loading up to 40 N then restores in temperature arises during frictional contacts makes carbon and carbide to plasticity state under room temperature provides self-lubricant properties.